An in situ encapsulation approach for polysulfide retention in lithium–sulfur batteries. Issue 14 (30th March 2020) - Ren, Y. X.; Jiang, H. R.; Xiong, C.; Zhao, C.; Zhao, T. S.
Abstract : An in situ encapsulation strategy is adopted for protecting sulfur/carbon composite cathodes, extending the cycle life with a minor sacrifice in the rate capability. Abstract : A long-life lithium–sulfur battery requires insulation of the dissolved polysulfide intermediates from the reactive anode. However, there exists a trade-off between preventing polysulfide dissolution and facilitating the sulfur redox reactions. Here, an in situ encapsulation strategy for sulfur/carbon (S/C) composite cathode is developed. We employ antimony trifluoride as a bi-functional pre-coating layer on the S/C composite surface. During the in situ encapsulation process, the liquid electrolyte can wet the S/C composite; while being catalyzed by antimony trifluoride, the liquid electrolyte can polymerize to form a dense lithium-ion-conducting solid polymer electrolyte (SPE) layer on the S/C composite surface. Additionally, antimony trifluoride proves to have strong anchoring effects on polysulfides, which works together with the SPE layer to suppress polysulfide dissolution. The in situ encapsulated cathode enhances the cyclability with a minor sacrifice in the rate capability. It is further demonstrated that the cathode can be directly paired with a non-protected lithiated silicon anode to achieve a practical capacity retention rate of 87% for 200 cycles.